Some aspects of cesium-137 entry into “market basket” in Kyiv - Buzynnyi, M.G.; Mietelski, J.W.; Kimura, S.; Mykhailova, L.L. (Environment & Health, 2019)
Objective: We studied the peculiarities of the entry of wild mushrooms and berries to the markets, analyzed, and evaluated the concentration of 137Cs in wild mushrooms and berries which were sold in several markets of Kyiv city.Materials and methods: We sampled the sets of wild mushrooms: chanterelle (Cantharellus cibarius), king bolete (Boletus edulis), bay bolete (Xerocomus badius), aspen mushroom (Leccinum aurantiacum), honey agaric (Armillaria mellea), orange agaric (Lactarius deliciosus), slippery jack (Suillus luteus), and berries: european blueberry (Vaccinium myrtillus), cranberry (Vaccinium oxycoccos), lingonberry (Vaccinium vitis-idaea) and bog bilberry (Vaccinium uliginosum) that were sold at 5 markets of Kyiv in summer-autumn period of 2018. The concentration of 137Cs in the samples was estimated with the help of gamma-spectroscopic method, averaging was performed by the types of the products and by the markets. A survey on the collection and delivery of forest products to the markets was carried out among the sellers.Results: 153 samples, including 87 mushrooms and 66 berries, were taken at 5 markets of Kyiv. 137Cs concentrations in the products and their conformity to the sanitary standards were determined. Sanitary standard of 137Cs content was exceeded in 14.8% of 54 blueberries samples and in 25% of 80 mushroom samples, in particular, in 46.2% of 26 samples of chanterelles and in 54.5% of 11 samples of bay bolete (Xerocomus badius) mushrooms. The most contaminated forest products were sold near “Lisova” underground station. 137Cs contamination of the products depended on the place of gathering and the prior routes of products’ delivery.
Keywords: 137Cs; wild mushrooms and berries; "market basket"; Chornobyl